In operando visualization of electrolyte stratification dynamics in lead-acid battery using phase-contrast X-ray imaging. Issue 66 (21st July 2020) - Takamatsu, Daiko; Hirano, Tatsumi; Yoneyama, Akio; Kimura, Takayuki; Harada, Motoko; Terada, Masayuki; Okoshi, Tetsuro
Abstract : Real-time visualization of electrolyte stratification dynamics under lead-acid battery operation with high temporal and spatial resolution by phase-contrast X-ray imaging. Abstract : An understanding of electrolyte stratification behaviours in lead-acid battery electrolytes during battery operation is important for optimal operation and design of lead-acid batteries for vehicle applications. In this paper, we present an in operando phase-contrast X-ray imaging technique for quantitatively visualizing electrolyte stratification dynamics that arise in electrolytes during battery operation.